Eradicating the Spread of LGBT Through Maqashid Ash-Shari’ah Based Family Law: A Transcendental Prophetic Review - Firmansyah, Indra; Prasetyoningsih, Nanik; Miftah Farid, Achmad (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
Islam regulates human behavior, including biological relationships and offspring preservation. LGBT individuals face discrimination in society, with 3% of Indonesians being LGBT. LGBT activists often seek human rights that contradict Islamic law, accusing Islam of obstructing freedom of opinion. Islam disagrees with curbing natural sexual instincts, viewing them as gifts from Allah.This study aims to analyze the phenomenon of Lesbian, Gay, Bisexual, and Transgender (LGBT) as a moral deviation in Maqashid Ash-Shari’ah society under the perspective of, or seeking the purpose and wisdom of Islamic Rules related to this deviant phenomenon. Generally, this study explores the meaning of Islam in responding to deviations in humanity, including the LGBT which was classified as deeds cursed by Allah SWT.